The Best Interests of a Child in Alternative Care and Intercountry Adoption – A Model for a Uniform Approach - Glynis van der Walt (Obiter, 2024)
Where a child is orphaned or abandoned, an obligation rests on the State to provide appropriate alternative care for the child concerned. It is of fundamental importance that a child who is found to be struggling emotionally, economically, physically and psychologically be protected. Such children need, and have a legal right, to be cared for and protected. Governments have a legal obligation to respond. Both international and national law recognise the standard of the best interests of a child and the principle is fundamental when determining inter alia whether alternative care for the child concerned is the most appropriate option. However, the best-interests principle is a vague and indeterminate concept, allowing for decisions to be based on a subjective approach. A model is proposed in the article in an attempt to provide a uniform approach for reaching a decision regarding the placement of an orphaned or abandoned child in appropriate alternative care.